A review on divisible load theory applications. - Shokripour, Amin; Othman, Mohamed (International Information Institute, 2009)
During the last decade, using parallel and distributed system has been general. In these systems, a huge size of data is distributed between many systems for getting better performance. Dividing data is one of the challenges in this type of system, because efficiency of system has direct relation to distributed data. One of proposed method for managing data distribution called Divisible Load Theory (DLT). This method is based on the actuality that data in some applications can be divided arbitrarily to some independent parts that each of them can be processed independently from others. In this paper, we present a survey on DLT applications. In addition, the article will discuss about some fundamental concepts for understanding DLT papers.